Adolescent Information Management and Parental Knowledge in Non-Latino White and Latino Youth Managing Type 1 Diabetes. (31st August 2017) - Tucker, Christy; Wiebe, Deborah J; Main, Alexandra; Lee, Alyssa G; White, Perrin C
Abstract: Objectives: The objective of this study is to examine associations between adolescents' regulation of information about their type 1 diabetes (adolescent disclosure, secrecy), parental knowledge about their adolescent's diabetes management, diabetes outcomes (adherence, HbA1c), and depressive symptoms in Non-Latino White and Latino families. Methods: In all, 118 adolescents (56 = Latino, 62 = Non-Latino White) completed surveys of disclosure to and secrecy from parents, parental knowledge of adolescent diabetes management, adherence, and depressive symptoms, and mothers completed measures of maternal knowledge and adolescent adherence. Glycemic control was extracted from medical records. Adolescents also completed structured interviews about parental knowledge about their diabetes-related problems. Results: Interviews revealed that adolescent disclosure is the primary method by which parents gain knowledge about adolescent diabetes management problems. Adolescent disclosure to and secrecy from parents were uniquely associated with diabetes management and depressive symptoms independent of parental knowledge across ethnic groups; maternal reports of knowledge about her adolescent's diabetes care activities were associated with diabetes management independent of adolescent disclosure and secrecy. Conclusions: Adolescent information management strategies are a primary means by which parents gain knowledge about diabetes, which may facilitate more effective management.